A FeCoNi-based alloy with multi-scale heterogeneous structure and preparation method thereof

Through multi-pass cold rolling and heat treatment processes, a FeCoNi-based high-entropy alloy with multi-scale heterostructure was constructed, which solved the problem of insufficient yield strength and ductility in extreme structural applications of existing high-entropy alloys, achieved high strength and good plasticity, and improved the comprehensive mechanical properties and reliability of the material.

CN116555658BActive Publication Date: 2025-04-08SHANGHAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310542547.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-15
Publication Date
2025-04-08
Estimated Expiration
2043-05-15

AI Technical Summary

Technical Problem

Existing high-entropy alloys are insufficient in extreme structural applications, and there are strain softening problems, resulting in unreliability and safety risks of material use.

Method used

Using multi-pass cold rolling and heat treatment processes, FeCoNi-based high-entropy alloys with multi-scale heterostructures are designed. Through fine composition and thermal machining processes, a micro-to-nanoscale heterostructure is constructed to achieve high strength and good plasticity.

Benefits of technology

It achieves high yield strength and tensile strength, maintains a good elongation, solves the problem of strain softening, and improves the comprehensive mechanical properties and reliability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116555658B_ABST
    Figure CN116555658B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a FeCoNi-based alloy with a multi-scale heterogeneous structure, which relates to the technical field of high entropy alloys. The alloy material of the invention has an atomic ratio of 1±0.005:1±0.005:1±0.005:0.2-0.3:0.2-0.3:0-0.15 for the six elements of Fe, Co, Ni, Al, Ti and Cu, and an impurity ratio of ≤0.2%, wherein the atomic ratio of the three elements of Fe, Co and Ni is 1:1:1. The invention controls the DP of the second phase at the grain boundary and the grain boundary type and distribution by optimizing and improving the composition, heat treatment and mechanical processing method, constructs an FeCoNi-based high entropy alloy with heterogeneous structures from micrometer to nanometer scale, prepares a multiphase microstructure alloy with a structural gradient, and has a simple and efficient process. The prepared alloy material has excellent comprehensive properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high entropy alloys, and in particular to a method for preparing a FeCoNi-based alloy with a multi-scale heterogeneous structure. Background Art

[0002] In recent years, the concept of high entropy alloys (HEAs) has enabled the selection of alloy components to move towards a broad space in the middle of the phase diagram, providing a good space for adjusting composition-structure-performance. In the random solid solution state, the mixing entropy of HEA greatly expands the solubility range of the terminal solid solution or intermetallic compound, thereby forming a simple solid solution. Among them, the face-centered cubic (FCC) HEA has considerable ductility, excellent corrosion resistance and radiation resistance, but insufficient strength. Therefore, the strategy of enhancing the toughness of the FCC matrix phase is usually adopted to design HEAs with excellent performance. Among the various strengthening methods, precipitation strengthening plays a very important role, because the characteristics of multiple main elements in HEA and the slow diffusion effect of elements provide the opportunity to form fine and stable nanoscale precipitates, pushing the strength of the alloy to a new high level. Nanoscale precipitation, as a sustainable dislocation source, can simultaneously improve ductility and strength. Among them, from 77K to ambient temperature, by the coherent L1 2 The strength of precipitation-hardened HEAs enhanced by nano-precipitates has shown great potential.

[0003] However, the coherent L1 2 The nanoprecipitates are only stable at low temperatures. 0.3 In CoCrFeNi alloy, L1 2 The phase is only stable below 600°C. Under appropriate external conditions or when the composition changes, the metastable coherent L1 2 Nanoprecipitates of this type will transform into hard intermetallic compounds at the micron scale, deteriorating the comprehensive mechanical properties. In extreme structural applications, it is still very challenging to achieve high yield strengths >1.1GPa and reasonable ductility. In addition, HEAs reinforced with nanoprecipitates have serious strain softening problems, which make these materials prone to accidental overloading and undesirable plastic instability. Once plastic deformation begins, rapid and continuous necking to a certain point will occur, which inevitably leads to poor uniform elongation, and there are serious unreliability and safety hazards in long-term use. Summary of the invention

[0004] In order to solve the problems of the prior art, the purpose of the present invention is to overcome the shortcomings of the existing technology and provide a method for preparing a FeCoNi-based alloy with a multi-scale heterogeneous structure, specifically a high-entropy alloy composition design, heat treatment and mechanical processing method with heterogeneous structures from micron to nanometer scales. The FeCoNi-based alloy prepared by this method has excellent yield strength, tensile strength and elongation.

[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0006] A method for preparing a FeCoNi-based alloy with a multi-scale heterogeneous structure comprises the following nine steps:

[0007] Step 1: The composition of the FeCoNi-based alloy is as follows: the atomic ratio of the six elements Fe, Co, Ni, Al, Ti and Cu is 1±0.005:1±0.005:1±0.005:0.2-0.3:0.2-0.3:0-0.15, and the impurities are ≤0.2%;

[0008] Step 2, smelting the FeCoNi-based alloy in an argon atmosphere to obtain a smelted alloy;

[0009] Step 3, sucking and casting the molten alloy into a copper mold to obtain an initial alloy;

[0010] Step 4, subjecting the initial alloy to a first multi-pass cold rolling treatment, wherein the total reduction of the first multi-pass cold rolling treatment is 50-60%, to obtain a first cold rolled alloy;

[0011] Step 5: subjecting the first cold-rolled alloy to a homogenization treatment at 1150-1200° C. for 2-4 hours to obtain a homogenized alloy;

[0012] Step 6, subjecting the homogenized alloy to a second multi-pass cold rolling treatment, wherein the total reduction of the second multi-pass cold rolling treatment is 50-80%, to obtain a second cold rolled alloy;

[0013] Step 7, subjecting the second cold-rolled alloy to a rapid recrystallization treatment at 1150-1200° C. for 30-45 seconds in an argon atmosphere to obtain a recrystallized alloy;

[0014] Step 8, subjecting the recrystallized alloy to an aging treatment at 780-800° C. for 2-12 h to obtain an aging-treated alloy;

[0015] Step nine: water quenching the aging treated alloy to obtain the FeCoNi-based alloy with a multi-scale heterogeneous structure.

[0016] Preferably, the thickness of the second cold rolled alloy is within 20% of the thickness of the initial alloy.

[0017] Preferably, the reduction amount of a single pass of the multi-pass cold rolling treatment is 10%, and the single cold rolling time is 10±1 min.

[0018] Preferably, the smelting treatment is repeated smelting 5-6 times in a non-consumable vacuum arc melting furnace and argon atmosphere protection, each smelting lasts 2-3 minutes, and the smelting parameters are: the current value is 150-210A.

[0019] The present invention also provides a technical solution, a FeCoNi-based alloy with a multi-scale heterogeneous structure, which is prepared by using the above-mentioned preparation method of the FeCoNi-based alloy with a multi-scale heterogeneous structure.

[0020] The FeCoNi-based alloy having a multi-scale heterogeneous structure includes micron-scale heterogeneous FCC equiaxed crystals, submicron-scale L2 1 Phase and nanoscale L1 2 Mutually.

[0021] Preferably, the heterogeneous FCC equiaxed crystals have two different size ranges, with the small grain size being 8 to 25 μm and the large grain size being 25 to 60 μm.

[0022] Preferably, the submicron L2 1 Phase size is less than 2 microns, nanoscale L1 2 The phase size is about 40-45 nm.

[0023] Preferably, the submicron L2 1 The volume fraction of the phase is about 5.5-15.2%, and the nanoscale L1 2 The volume fraction of the phase is about 40 to 55%.

[0024] Preferably, the yield strength of the FeCoNi-based alloy with a multi-scale heterogeneous structure is ≥1144 MPa, the tensile strength is ≥1442 MPa, and the elongation is ≥15%.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a preparation method of a FeCoNi-based alloy with a multi-scale heterogeneous structure. The process is simple and efficient. Through the design of fine composition and thermal mechanical processing technology, the DP of the second phase at the grain boundary and the grain boundary type and distribution are controlled to construct a FeCoNi-based high entropy alloy with heterogeneous structures from micron to nanometer scales. After simple cold rolling and heat treatment processes, a multiphase microstructure alloy with a structural gradient is prepared. The alloy includes micron-scale heterogeneous FCC equiaxed grains, submicron-scale L21 Phase (A 2 BC type), nano-scale L1 2 Phase (A 3 The organic combination of the three (type B) achieves high strength and maintains good plasticity under the synergistic effect of the three mechanisms of grain refinement, back stress strengthening and second phase strengthening. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is an EBSD photograph of the FCC grain structure of the FeCoNi-based alloy of Example 1 of the present invention;

[0028] Figure 2 This is a scanning electron microscope photograph of the phase distribution of the FeCoNi-based alloy of Example 1 of the present invention;

[0029] Figure 3 This is an EBSD photograph of the FCC grain structure of the FeCoNi-based alloy of Example 2 of the present invention;

[0030] Figure 4 This is a scanning electron microscope photograph of the phase distribution of the FeCoNi-based alloy of Example 2 of the present invention;

[0031] Figure 5 This is a scanning electron microscope photograph of the phase distribution of the FeCoNi-based alloy of Example 3 of the present invention;

[0032] Figure 6 It is a tensile engineering stress-strain curve diagram of the FeCoNi-based alloy of Examples 1-3 of the present invention and Comparative Example 1;

[0033] Figure 7 This is a scanning electron microscope photograph of the phase distribution of the FeCoNi-based alloy of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] For ease of understanding, let us first explain the English terms mentioned below:

[0036] HEA: high entropy alloy;

[0037] FCC: face-centered cubic lattice.

[0038] Embodiment 1:

[0039] This embodiment provides a method for preparing a FeCoNi-based alloy having a multi-scale heterogeneous structure, wherein the components of the FeCoNi-based alloy are, by atomic percentage, 28.6% Fe, 28.7% Co, 28.7% Ni, 7% Al, and 7% Ti;

[0040] The FeCoNi-based alloy is smelted in an argon atmosphere, and the smelting is repeated 5 times;

[0041] After the smelting treatment, the smelted FeCoNi-based alloy was suction cast into a copper mold of 5 mm × 10 mm × 90 mm, and subjected to the first multi-pass cold rolling treatment, with a total reduction of 50%, i.e., cold rolled to a thickness of 2.5 mm;

[0042] The FeCoNi-based alloy after the first cold rolling treatment was subjected to a homogenization treatment at 1150°C for 2 hours;

[0043] The FeCoNi-based alloy after homogenization is subjected to a second multi-pass cold rolling process, with a total reduction of 60% and cold rolling to a thickness of 1 mm;

[0044] The FeCoNi-based alloy after the second multi-pass cold rolling treatment was subjected to a rapid recrystallization treatment at 1150°C for 30s in an argon atmosphere;

[0045] The FeCoNi-based alloy after rapid recrystallization treatment was subjected to aging treatment at 800°C for 2 h;

[0046] Finally, the FeCoNi-based alloy after aging treatment is water quenched.

[0047] The size of the heterogeneous FCC equiaxed grains in the FeCoNi-based alloy structure obtained in Example 1 is as follows: Figure 1 As shown, the average size of the small grain area is about 24.8μm, and the average size of the large grain area is 58.3μm; Figure 2 As shown, the sub-micron L2 1 Phase (A 2 BC type) size is less than 2 microns, nanometer-level L1 2 Phase (A 3 B type) is about 41.886nm in size. After calculation, the submicron L2 1 The volume fraction of the phase is about 15.2%, and the nanoscale L1 2 The volume fraction of the phase is about 49%. At the same time, the stress-strain curve is as follows Figure 6 As shown in No. 2, the yield strength reaches 1196 MPa, the tensile strength reaches 1505 MPa, and the elongation remains at 13.69%.

[0048] Embodiment 2:

[0049] This embodiment provides a method for preparing a FeCoNi-based alloy with a multi-scale heterogeneous structure, wherein the components of the FeCoNi-based alloy are, by atomic percentage, 27.8% Fe, 27.8% Co, 27.8% Ni, 6.8% Al, 6.8% Ti, and 3% Cu;

[0050] The FeCoNi-based alloy is smelted in an argon atmosphere and smelted repeatedly for 6 times;

[0051] After the smelting treatment, the smelted FeCoNi-based alloy was suction cast into a copper mold of 5 mm × 10 mm × 90 mm, and subjected to the first multi-pass cold rolling treatment, with a total reduction of 50%, i.e., cold rolled to a thickness of 2.5 mm;

[0052] The FeCoNi-based alloy after the first cold rolling treatment was subjected to a homogenization treatment at 1200°C for 4 hours;

[0053] The FeCoNi-based alloy after homogenization is subjected to a second multi-pass cold rolling process, with a total reduction of 80% and cold rolling to a thickness of 0.5 mm;

[0054] The FeCoNi-based alloy after the second multi-pass cold rolling treatment was subjected to a rapid recrystallization treatment at 1200°C for 40s in an argon atmosphere;

[0055] The FeCoNi-based alloy after rapid recrystallization treatment was subjected to aging treatment at 800°C for 8h;

[0056] Finally, the FeCoNi-based alloy after aging treatment is water quenched.

[0057] The size of the heterogeneous FCC equiaxed grains in the FeCoNi-based alloy structure obtained in Example 2 is as follows: Figure 3 As shown, the average size of the small grain area is about 8.6μm, and the average size of the large grain area is 25.3μm; Figure 4 As shown, the sub-micron L2 1 Phase (A 2 BC type) size is about 1.5 microns, nanometer-scale L1 2 Phase (A 3 B type) is about 43.572nm. After calculation, the submicron L2 1 The volume fraction of the phase is about 8.7%, and the nanoscale L1 2 The volume fraction of the phase is about 55%. At the same time, the stress-strain curve is as follows Figure 6 As shown in No. 1, the yield strength reaches 1298 MPa, the tensile strength reaches 1615 MPa, and the elongation remains at 17.03%.

[0058] Embodiment 3:

[0059] This embodiment provides a method for preparing a FeCoNi-based alloy with a multi-scale heterogeneous structure, wherein the components of the FeCoNi-based alloy are, by atomic percentage, 27.5% Fe, 27.5% Co, 27.6% Ni, 6.7% Al, 6.7% Ti, and 4% Cu;

[0060] The FeCoNi-based alloy is smelted in an argon atmosphere, and the smelting is repeated 5 times;

[0061] After the smelting treatment, the smelted FeCoNi-based alloy was suction cast into a copper mold of 5 mm × 10 mm × 90 mm, and subjected to the first multi-pass cold rolling treatment, with a total reduction of 60%, i.e., cold rolling to a thickness of 2 mm;

[0062] The FeCoNi-based alloy after the first cold rolling treatment was subjected to a homogenization treatment at 1200°C for 4 hours;

[0063] The FeCoNi-based alloy after homogenization is subjected to a second multi-pass cold rolling process, with a total reduction of 50% and cold rolling to a thickness of 1 mm;

[0064] The FeCoNi-based alloy after the second multi-pass cold rolling treatment was subjected to a rapid recrystallization treatment at 1200°C for 45s in an argon atmosphere;

[0065] The FeCoNi-based alloy after rapid recrystallization treatment was subjected to aging treatment at 780°C for 12 h;

[0066] Finally, the FeCoNi-based alloy after aging treatment is water quenched.

[0067] The size of the heterogeneous FCC equiaxed grains in the FeCoNi-based alloy structure obtained in Example 3 is as follows: Figure 5 As shown, the sub-micron L2 1 Phase (A 2 BC type) size is about 1 micron, nanometer-scale L1 2 Phase (A 3 B type) is about 44.369nm in size. After calculation, the submicron L2 1 The volume fraction of the phase is about 5.5%, and the nanoscale L1 2 The volume fraction of the phase is about 40%. At the same time, the stress-strain curve is as follows Figure 6 As shown in No. 3, the yield strength reaches 1144 MPa, the tensile strength reaches 1442 MPa, and the elongation remains at 16.96%.

[0068] Comparative Example 1:

[0069] This comparative example provides a method for preparing a FeCoNi-based alloy having a multi-scale heterogeneous structure, wherein the components of the FeCoNi-based alloy are, by atomic percentage, 27.8% Fe, 27.8% Co, 27.8% Ni, 6.8% Al, 6.8% Ti, and 3% Cu;

[0070] The FeCoNi-based alloy is smelted in an argon atmosphere and smelted repeatedly for 6 times;

[0071] After the smelting treatment, the smelted FeCoNi-based alloy was suction-cast into a copper mold of 5 mm × 10 mm × 90 mm and homogenized at 1150 ° C for 4 hours;

[0072] The FeCoNi-based alloy after homogenization is subjected to multiple cold rolling processes, with a total reduction of 80% and cold rolling to a thickness of 1 mm;

[0073] The FeCoNi-based alloy after multiple cold rolling was subjected to rapid recrystallization treatment at 1200°C for 120s in an argon atmosphere.

[0074] The FeCoNi-based alloy after rapid recrystallization treatment was subjected to aging treatment at 800°C for 8h;

[0075] Finally, the FeCoNi-based alloy after aging treatment is water quenched.

[0076] The FeCoNi-based alloy structure obtained in Comparative Example 1 is as follows: Figure 7 As shown, no heterogeneous grain structure is shown, and the stress-strain curve is shown in Figure 6 As shown in 4#, the yield strength of comparative example 1 is much lower than the yield strength of examples 1 to 3.

[0077] Furthermore, in the above-mentioned embodiments and comparative examples, the smelting treatment is repeated smelting in a non-consumable vacuum arc melting furnace and an argon atmosphere protection, and the current value is 150-210A.

[0078] Furthermore, in the above-mentioned embodiments and comparative examples, the reduction amount of a single pass of the multi-pass cold rolling treatment is 10%, and the single cold rolling time is 10±1 min.

[0079] Furthermore, in the above embodiments and comparative examples, the size of the copper mold used is: 5mm×10mm×90mm.

[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is limited by the attached embodiments and their equivalents.

Claims

1. A method for preparing a FeCoNi-based alloy with a multi-scale heterogeneous structure, characterized in that: It includes the following nine steps: Step 1: The composition of the FeCoNi-based alloy is as follows: the atomic ratio of the six elements Fe, Co, Ni, Al, Ti and Cu is 1±0.005:1±0.005:1±0.005:0.2-0.3:0.2-0.3:0-0.15, and the impurities are ≤0.2%; Step 2, smelting the FeCoNi-based alloy under an argon atmosphere to obtain a molten alloy; Step 3, sucking and casting the molten alloy into a copper mold to obtain an initial alloy; Step 4, subjecting the initial alloy to a first multi-pass cold rolling treatment, wherein the total reduction of the first multi-pass cold rolling treatment is 50-60%, to obtain a first cold rolled alloy; Step 5: subjecting the first cold-rolled alloy to a homogenization treatment at 1150-1200° C. for 2-4 hours to obtain a homogenized alloy; Step 6, subjecting the homogenized alloy to a second multi-pass cold rolling treatment, wherein the total reduction of the second multi-pass cold rolling treatment is 50-80%, to obtain a second cold rolled alloy; Step 7, subjecting the second cold-rolled alloy to a rapid recrystallization treatment at 1150-1200° C. for 30-45 seconds in an argon atmosphere to obtain a recrystallized alloy; Step 8, subjecting the recrystallized alloy to an aging treatment at 780-800° C. for 2-12 h to obtain an aging-treated alloy; Step nine: water quenching the aging treated alloy to obtain the FeCoNi-based alloy with a multi-scale heterogeneous structure.

2. The method for preparing a FeCoNi-based alloy having a multi-scale heterogeneous structure according to claim 1, characterized in that: The thickness of the second cold rolled alloy is within 20% of the thickness of the initial alloy.

3. The method for preparing a FeCoNi-based alloy having a multi-scale heterogeneous structure according to claim 1, characterized in that: The reduction amount of a single pass of the multi-pass cold rolling process is 10%, and the single cold rolling time is 10±1 min.

4. The method for preparing a FeCoNi-based alloy having a multi-scale heterogeneous structure according to claim 1, characterized in that: The smelting process is repeated smelting 5-6 times in a non-consumable vacuum arc melting furnace and argon atmosphere protection, each smelting time is 2-3 minutes, and the smelting parameters are: the current value is 150-210A.

5. A FeCoNi-based alloy with a multi-scale heterogeneous structure, prepared by the preparation method of the FeCoNi-based alloy with a multi-scale heterogeneous structure according to any one of claims 1 to 4, characterized in that: The FeCoNi-based alloy with a multi-scale heterogeneous structure comprises micron-scale heterogeneous FCC equiaxed crystals, submicron-scale L21 phases and nanometer-scale L12 phases.

6. The FeCoNi-based alloy with a multi-scale heterogeneous structure according to claim 5, characterized in that: The heterogeneous FCC equiaxed crystals have two different scale ranges, with a small grain size of 8 to 25 μm and a large grain size of 25 to 60 μm.

7. The FeCoNi-based alloy with a multi-scale heterogeneous structure according to claim 5, characterized in that: The submicron-scale L21 phase has a size of less than 2 microns, and the nanoscale L12 phase has a size of about 40-45 nm.

8. The FeCoNi-based alloy with a multi-scale heterogeneous structure according to claim 5, characterized in that: The volume fraction of the submicron-scale L21 phase is about 5.5-15.2%, and the volume fraction of the nanoscale L12 phase is about 40-55%.

9. The FeCoNi-based alloy with a multi-scale heterogeneous structure according to claim 5, characterized in that: The yield strength of the FeCoNi-based alloy with a multi-scale heterogeneous structure is ≥1144MPa, the tensile strength is ≥1442MPa, and the elongation is ≥15%.

Citation Information

Patent Citations

  • L12 particle strongly-plasticized medium-entropy alloy and preparation method thereof

    CN114457270A

  • High-toughness heterogeneous multiphase core-shell structure medium-entropy alloy and preparation method thereof

    CN115198162A